Farmers' Perceptions of the Implementation of Organic Rice Development in Bantaeng Regency - juswansar; Ratnawati Tahir; Nurdin; Sri Mardiyati; Amruddin (International Journal of Economics, Business and Innovation Research, 2025)
This research aims to analyze farmers' perceptions of the implementation of organic rice development, identify factors that influence farmers' perceptions of the implementation of organic rice development in Bantaeng Regency, and analyze factors that influence farmers' perceptions of the implementation of organic rice farming in Bantaeng Regency. This research starts from October to November 2024 using quantitative methods. The data collection method uses the library or literature study method, observation, questionnaires and in-depth documentation using a questionnaire that has been tested for validity and reliability, while the data analysis method uses a Likert scale and multiple linear regression. The results of the analysis using multiple linear regression tests show that the level of farmers' perception of the implementation of organic rice development in Bantaeng Regency is relatively high, with an aggregate average of 69.60%. Meanwhile, the factors that influence farmers' perceptions of the implementation of organic rice development in Bantaeng Regency are innovation characteristics.